2020
DOI: 10.1021/acs.est.9b07127
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation Changes Bioaccumulation and Toxicity of Diclofenac in Aquatic Organisms

Abstract: Biotransformation plays a crucial role in regulating the bioaccumulation potential and toxicity of organic compounds in organisms but is, in general, poorly understood for emerging contaminants. Here, we have used diclofenac as a model compound to study the impact of biotransformation on the bioaccumulation potential and toxicity in two keystone aquatic invertebrates: Gammarus pulex and Hyalella azteca. In both species, diclofenac was transformed into several oxidation products and conjugates, including two no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…Furthermore, the in vitro system could potentially be limited in cofactors to provide for conjugation as well, explaining why the metabolite pattern of the hepatocytes could be less diverse for some substances. In other studies, a larger number of metabolites could be identified in both H. azteca and hepatocyte samples (Fu et al 2020). A more detailed metabolite pattern might have been detected in case a radiolabel had been used.…”
Section: Investigation Of Sources Of Bcf Differences: Effect Of Food mentioning
confidence: 82%
“…Furthermore, the in vitro system could potentially be limited in cofactors to provide for conjugation as well, explaining why the metabolite pattern of the hepatocytes could be less diverse for some substances. In other studies, a larger number of metabolites could be identified in both H. azteca and hepatocyte samples (Fu et al 2020). A more detailed metabolite pattern might have been detected in case a radiolabel had been used.…”
Section: Investigation Of Sources Of Bcf Differences: Effect Of Food mentioning
confidence: 82%
“…[ 3,4 ] For instance, the pharmaceutical diclofenac is one of the most popular non‐steroidal anti‐inflammatory drugs with a global annual consumption of up to 1000 tons, and it is frequently detected in the treated wastewater, rivers, lakes, and even drinking water. [ 5,6 ] Norfloxacin is a kind of fluoroquinolone antibiotics used in the treatment of bacterial infections, aquaculture industry, and livestock, which is often detected in wastewater effluents. [ 7 ] Because these chemical productions are toxic and refractory to traditional biological treatment, it is urgent to develop efficient and environment‐friendly treatment technology.…”
Section: Introductionmentioning
confidence: 99%
“…Its testicular and epididymal toxicity also attract people's attention (Owumi et al 2020). Fu et al (2020) found DCF residue in water to be biotransformed by Gammarus pulex and Hyalella Azteca, representing a 25 to 110-fold increase of bioconcentration factors. Thus, the safe and effective removal of DCF residue has been a rising concern.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%